Clinical and radiological evaluation of bovine hoofs: A postmortem study (FAVE Sección Ciencias Veterinarias, 2025)
The aim of this study was to evaluate the findings obtained from clinical, radiographic and cross-sectional examination of 36 cattle hoofs randomly taken from the slaughterhouse. In the study, it was determined that there were significant differences in the distribution ranges and frequencies, although the averages were normal when looking at the structural characteristics of the hoofs (hoof angle, dorsal wall length, etc.). Also, clinical examination of the base and examination of the cross-sectional surface of the hoof according to hoof radiography revealed different findings. In conclusion, this study demonstrated that hoof care is not only a treatment method for foot and hoof diseases but also a routine procedure in cattle breeding.
Keywords: bovine; dorsal wall length; hoof; hoof angle